Gastrointestinal toxicities from targeted therapies: measurement, duration and impact. Issue 2 (June 2015) - Bossi, Paolo; Lucchesi, Maurizio; Antonuzzo, Andrea
Abstract : Purpose of review: Gastrointestinal toxicities deriving from targeted therapies are main issues in the oncologic setting, as they can negatively impair quality of life, reducing patient's adherence to treatment and dose intensity, so ultimately possibly affecting outcome. We reviewed some methodological questions linked to the assessment of this kind of toxicity, in terms of way of measurement, duration of the assessed toxicity and impact on the global treatment program. Recent findings: The scale of toxicity assessment may influence the evaluation itself; reporting the adverse events by the physician is generally less accurate than by the patient, and these two modalities should be integrated in the analysis of gastrointestinal toxicities by targeted treatment. Moreover, the duration of the symptoms and the attention to the lower grade toxicities estimation are generally underreported in clinical trials. The factors that may affect treatment's adherence by the patient are discussed, as they are strictly linked to the appearance and intensity of gastrointestinal toxicities. Summary: Methodological issues should be considered in designing new trials with targeted therapies and evaluating the way of assessment of adverse events, mainly gastrointestinal.